Chemical ecology and conservation biogeography of Rhododendron ponticum L. - Egan, Paul A. (Trinity College (Dublin, Ireland). Department of Botany, 2015)
The general aims of this thesis were two-fold; firstly, to further knowledge on the topic of toxic nectar in plants, utilizing Rhododendron ponticum (and associated taxa) as a model for these investigations; and secondly, to assess climatic suitability for this species within its native range under climate change, as a model scenario to inform best-practice in conservation. This shrubby species occurs as a Tertiary relict in the Iberian Peninsula, but is widely naturalised and invasive throughout Ireland, Britain and parts of NW Europe. This contrasting duality in distribution afforded the opportunity for a number of comparative assessments to be made between the native and invasive range of R. ponticum; and therefore constituted the basis of a number of research questions that were assessed.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin